1997
DOI: 10.1124/mol.52.2.259
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Conserved Aromatic Residues Essential for Agonist Binding and Second Messenger Production at 5-Hydroxytryptamine2AReceptors

Abstract: Several models of agonist binding to G protein-coupled 5-hydroxytryptamine [5-HT] (serotonin) receptors have highlighted the potential importance of highly conserved aromatic residues for ligand binding and agonist efficacy. In this study, we tested these models by constructing and characterizing a number of point mutations of conserved and nonconserved aromatic residues using the 5-HT2A receptor as a model system. Mutations of three highly conserved tryptophans (W200A, W336A, and W367A) proposed to reside nea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
127
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(143 citation statements)
references
References 24 publications
16
127
0
Order By: Relevance
“…Ser (Strader et al 1989;Choudhary et al 1993;Almaula et al 1996;Roth et al 1997), G-protein coupling (DRYXXIXXPI153) (Moro et al 1993) and desensitization/internalization (NPXXY412) (Barak et al 1994) were conserved in both SER-2 and SER-2a (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…Ser (Strader et al 1989;Choudhary et al 1993;Almaula et al 1996;Roth et al 1997), G-protein coupling (DRYXXIXXPI153) (Moro et al 1993) and desensitization/internalization (NPXXY412) (Barak et al 1994) were conserved in both SER-2 and SER-2a (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…Various aromatic amino acids in the fourth and other TM domains have been studied for ligand binding and signaling in a large variety of GPCRs, including the m 1 and m 3 muscarinic, 5-HT 2 serotonergic, NK 2 tachykinin, and ␦-opioid receptors (Wess et al, 1992(Wess et al, , 1993Choudhary et al, 1993;Matsui et al, 1995;Befort et al, 1996;Roth et al, 1997;Renzetti et al, 1999a,b). In similarity to the data presented here, Befort et al (1996) found that W173 of the ␦-opioid receptor (in an analogous position to W158 of CB 2 ) is involved in receptor- ligand recognition and that mutation of this amino acid reduced the receptor's binding affinity to many ␦ ligands.…”
Section: Discussionmentioning
confidence: 99%
“…f14d12.6(ok371) has a 1072 bp deletion that removes a portion of exons I-VI and predicted TMs I-V, whereas tyra-3(ok325) has a 781 bp deletion that removes portions of exons IV-V and TMs III-V. Therefore, both f14d12.6(ok371) and tyra-3(ok325) are predicted null alleles, because these TMs are essential for ligand binding (Strader et al, 1989;Choudhary et al, 1993;Almaula et al, 1996;Roth et al, 1997). Under standard conditions, tyra-3(ok325) and f14d12.6(ok371) animals exhibited no gross behavioral defects with respect to locomotion, feeding, or egg retention.…”
Section: Resultsmentioning
confidence: 99%